Pentingnya Pendidikan Al-Qur’an pada Anak Usia Dini di PPPA Raudhatul Jannah - Suryabudi, Yusuf Atma; Hendrian, Hendrian; Pratama, Hendra Kusuma; Abdullah, Muh. Rizky; Sabila, Unik Hanifah (Lembaga Yasin AlSys, 2022)
Al-Qur'anul Karim is the source and principle of teaching. Learning the Qur'an for early childhood is very important to note. Educating children to be close to the Qur'an is the duty of a mother and father. In the history of Islam, it has been proven that the influence of the younger generation in the field of progress in the nation's education is very large. Starting of course from childhood education. Children are the forerunner of the next generation of us all. The formation of religious characters and Qur'anic morals will improve the surrounding environment to become more civilized and uphold Islamic values. This research was conducted with the aim of knowing how the learning system and learning methods of the Qur'an exist at PPPA Raudhatul Jannah. The method that the researcher uses in this research is descriptive qualitative using a literature study approach. The data collection technique in this study was to collect and critically examine data sources relevant to early childhood Al-Qur'an learning and learning methods as well as by conducting interviews with the PPPA Raudhatul Jannah management to find out the implementation of Al-Qur'an learning with various methods available. The result is that with all the existing facilities and the teaching staff of PPPA Raudhatul Jannah, educating early childhood in terms of tahfidz and mental personality of children to be independent and independent.